Weight Loss Method: Beginner Boxer's Perception - Trisnar Adi Prabowo; Tomoliyus; Endang Rini Sukamti; Fauzi; Mikkey Anggara Suganda (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Boxing is a martial art that imposes strict rules on body weight. There are many methods that boxers lose weight. So that it becomes a challenge for novice boxers who have never competed in boxing. The purpose of this study was to specifically investigate amateur boxing athletes at the beginner on how to lose weight. This research method is descriptive qualitative with interviews and questionnaires containing several questions via google form. The subjects in the study were 70 boxers and consisted of 2 categories, the first category was active boxers who competed at POPWIL (Regional Student Sports Week) as many as, 28 boxers and Pre PORPROV (Provincial Sports Week) as In theboxethe boxersecond category, boxers have never participated in an amateur boxing competition. Based on the results of the study, the most widely used weight loss method for beginner boxers is to limit carbon which are and Is carried out during the initial period of exercise. The majority of boxers use more than 1 method of weight loss. The effects felt by boxers are dehydration and lack of enthusiasm. Boxers feel these effects after a few days when starting to lose weight. In carrying out the method of weight loss, many boxers are doubtful about the danger to the body. So the need for special counseling is healthy and gradugraduallyual manner. In addition, coaches, doctors or nutritionists, colleagues, colleagues parents need to be involved to monitor and motivate boxers. It is hoped that this research will become the basis for future research to discuss ail a ball healthy methods and strategies for boxers to lose weight.